ENHANCING THE ABSORPTION OF RUTIN AND EFFECTIVE CANCER MANAGEMENT THROUGH HYALURONIC ACID FUNCTIONALIZED NANOPARTICLES - BHUVANESWARI, S. SRI; KUMUDHA, D. (International Journal of Applied Pharmaceutics, 2024)
Objective: The objective of this study is to develop Rutin Nanoparticles (RTN) and coat them with Hyaluronic Acid (HA) to overcome rutin's solubility and bioavailability limitations, and to enhance its uptake by cancer cells through selective delivery mechanisms. Methods: RTN were synthesized employing soya lecithin and chitosan through the homogenization technique. To further enhance the delivery of rutin to cancer cells, the optimized nanoparticle formulation was coated with HA to enhance its accumulation in cancer cells. The nanoparticles were characterized in terms of particle size (PS) distribution, zeta potential (ZP), entrapment efficiency (EE), morphology, in vitro drug release and in vitro cytotoxicity activities. Results: The resulting RTN and HA-coated RTN (HA RTN) exhibited particle sizes of 202.8 nm and 714 nm, with Polydispersity index (PDI) values of 26.4% and 25.5%, respectively. These findings suggest favourable stability and potential for cellular uptake. Moreover, in vitro examinations of drug release showcased a prolonged release pattern consistent with the Higuchi kinetic model, indicating a mechanism where drug release is primarily governed by diffusion. The in vitro cytotoxicity assay revealed that the HA RTN formulation demonstrated superior efficacy in inhibiting MCF-7 cells compared to free rutin and the uncoated RTN, as evidenced by the respective IC50 values of 145µg, 342 µg, and 413 µg. Conclusion: These findings highlight the promising potential of the HA RTN formulation as an effective anti-cancer treatment, paving the way for further development and clinical application of rutin-loaded nanoparticles in cancer therapy.